Proses Pembakaran Batu Kapur di CV. Timbul Jaya Putra - Ashari, Priagung Lukman; Farahdiansari, Ardana Putri (Jurnal Teknologi dan Manajemen Sistem Industri, 2022)
Understanding of production and production of limestone processing services, transportation and general trade. However, in line with the national development wheel which opens up wide opportunities for other fields, the company does not rule out expanding in other fields. The company is estabhilised in trading companies for chemical products. With the existence of a mining location and also supported by adequate equipment facilities, this company believes that it can serve consumers according to the specifications determined by the consumer company. The purpose of this research is to understand about the Limestone Combustion Process and the function of limestone. The data collection method used is the direct participation of researchers on the object of research, field observations and interviews with the department responsible for managing the combustion process in CV. TIMBUL JAYA PUTRA. The results of the research conducted, it was found that the combustion process carried out by CV TIMBUL JAYA PUTRA was quite good. So, you can get quality limestone and be able to compete in the market.